2014
DOI: 10.3109/0886022x.2014.900426
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between methylenetetrahydrofolate reductase (MTHFR) A1298C gene polymorphism and type 2 diabetic nephropathy risk: a meta-analysis

Abstract: In the sensitivity analysis according to the Hardy-Weinberg equilibrium (HWE), the results were consistent with those in non-sensitivity analysis. However, in the sensitivity analysis according to the control source from hospital, sample size of case (100), sample size of case (5100), the MTHFR A1298C gene polymorphism was not associated with T2DN risk. In conclusion, the MTHFR A1298C gene polymorphism was not associated with T2DN risk. However, additional studies are required to firmly establish a correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Metaanalysis of MTHFR polymorphisms revealed significant heterogeneity between studies for both 677C>T and 1298A>C. Further, there was no evidence for publication bias for these polymorphisms. In consistent with our results, a series of earlier published meta-analyses provided evidence of association between MTHFR 677C>T polymorphism and DN risk in various ethnicities (39)(40)(41)(42)(43)(44)(45). With regards to MTHFR 1298A>C only one meta-analysis performed in which no association between MTHFR 1298A>C and DN risk was observed (44).…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 91%
See 1 more Smart Citation
“…Metaanalysis of MTHFR polymorphisms revealed significant heterogeneity between studies for both 677C>T and 1298A>C. Further, there was no evidence for publication bias for these polymorphisms. In consistent with our results, a series of earlier published meta-analyses provided evidence of association between MTHFR 677C>T polymorphism and DN risk in various ethnicities (39)(40)(41)(42)(43)(44)(45). With regards to MTHFR 1298A>C only one meta-analysis performed in which no association between MTHFR 1298A>C and DN risk was observed (44).…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 91%
“…In consistent with our results, a series of earlier published meta-analyses provided evidence of association between MTHFR 677C>T polymorphism and DN risk in various ethnicities (39)(40)(41)(42)(43)(44)(45). With regards to MTHFR 1298A>C only one meta-analysis performed in which no association between MTHFR 1298A>C and DN risk was observed (44). Higher levels of homocysteine in patients with DN were demonstrated in multiple studies (46)(47)(48).…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 90%
“…Methylenetetrahydrofolate reductase A1298C polymorphism and diabetes risk: evidence from a meta-analysis T2DM [77] Association between MTHFR C677T polymorphism and diabetic nephropathy in the Chinese population: An updated meta-analysis and review DN [78] Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and susceptibility to diabetic nephropathy in Chinese type 2 diabetic patients: a meta-analysis T2DM and DN [79] Increasing prevalence of gestational diabetes mellitus when carrying the T variant allele of the MTHFR gene C677T polymorphism: a systematic review and meta-analysis Gestational diabetes [80] Relationship between methylenetetrahydrofolate reductase (MTHFR) A1298C gene polymorphism and type 2 diabetic nephropathy risk: a meta-analysis T2DM and DN [81] A Meta-Analysis of Association between Methylenetetrahydrofolate Reductase Gene (MTHFR) 677C/T Polymorphism and Diabetic Retinopathy DR [82] Genetics of diabetic neuropathy: Systematic review, meta-analysis and trial sequential analysis DN [83] Methylenetetrahydrofolate reductase C677T polymorphism and type 2 diabetes mellitus in Chinese population: a meta-analysis of 29 case-control studies T2DM [84] Plausible relationship between homocysteine and obesity risk via MTHFR gene: a meta-analysis of 38,317 individuals implementing Mendelian randomization Obesity risk [85] Association of homocysteine with type 2 diabetes: a meta-analysis implementing Mendelian randomization approach T2DM [86] Effects of Common Polymorphisms in the MTHFR and ACE Genes on Diabetic Peripheral Neuropathy Progression: a Meta-Analysis DN [87] ACE I/D and MTHFR C677T polymorphisms are significantly associated with type 2 diabetes in Arab ethnicity: a meta-analysis T2DM [88] Methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism and diabetic nephropathy susceptibility in patients with type 2 diabetes mellitus T2DM and DN [89] Association between MTHFR C677T polymorphism and diabetic nephropathy or diabetes mellitus risk: need for clarification of data in a recent meta-analysis T2DM and DN [90] Methylenetetrahydrofolate reductase C677T polymorphism and diabetic retinopathy risk: a meta-analysis of the Chinese population DR [91] The relationship between methylenetetrahydrofolate reductase C677T polymorphism and diabetic retinopathy: A meta-analysis in multi-ethnic groups DR [92] MTHFR gene C677T polymorphism and type 2 diabetic nephropathy in Asian populations: a meta-analysis DN [93] Genetic susceptibility to type 2 diabetes: a global meta-analysis studying the genetic differences in Tunisian populations T2DM [94] Genetic risk of type 2 diabetes in populations of the African continent: A systematic review and meta-analyses T2DM…”
Section: Study Title Associated Disease Referencementioning
confidence: 99%
“…7 However, studies conducted in several populations yielded contradictory outcomes in association with progression of DN and genetic polymorphisms. 8 Although several factors are involved in the pathophysiology of DN, the methylenetetrahydrofolate reductase (MTHFR) gene plays an important role in DN susceptibility through regulating the intracellular folate homeostasis and metabolism. 9 Globally, studies have attempted to find the relationship between reduced MTHFR activity and genetic polymorphisms of the MTHFR gene.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the genetic factors are concerned, it has been clearly shown that candidate gene polymorphisms have a major impact associated with disease progression diabetic nephropathy . However, studies conducted in several populations yielded contradictory outcomes in association with progression of DN and genetic polymorphisms …”
mentioning
confidence: 99%